COMPARATIVE EVALUATION OF THE ANTIBACTERIAL EFFICACY AND PHYTOCHEMICAL PROFILE OF METHANOL AND AQUEOUS EXTRACTS OF Vernonia amygdalina AGAINST GASTROENTERITIS CAUSING BACTERIA - Adoyi, Michael Paul; John, Ubelejit Alfred; Suwaiba, Ladan Muhammad; Tyohemba, Samuel Terhide; Kwaya, Vawanje Bitrus; Mbahi, Asugu Mary (FUDMA JOURNAL OF SCIENCES, 2025)
Vernonia amygdalina, commonly known as bitter leaf, is a shrub recognized for its bioactive compounds with documented antibacterial properties against gastroenteritis. However, the efficacy of methanolic and aqueous extracts of Vernonia amygdalina leaves has not been extensively evaluated. This study aimed to assess the efficacy of these extracts and determine their chemical composition, as well as their potential to inhibit the activity of selected bacteria associated with gastroenteritis. Vernonia amygdalina leaves were procured from Gombe central market, and the extracts were subjected to phytochemical screening. Three distinct bacterial isolates (Salmonella typhi, Escherichia coli, and Staphylococcus aureus) associated with gastroenteritis were obtained from the microbiology laboratory at Gombe State University and used in an antibacterial assay of the leaf extracts at varying concentrations (12.5 mg/mL, 25 mg/mL, 50 mg/mL, and 100 mg/mL), conducted using the agar well diffusion method. The results confirmed the presence of tannins, alkaloids, flavonoids, steroids, and saponins, and their antimicrobial action on the isolates. The methanol extract demonstrated a significantly higher inhibition zone of 15.1 mm at 100 mg/mL against E. coli, compared to 14.0 mm for the aqueous extract against S. typhi, suggesting methanol as a more effective solvent for extracting antibacterial compounds from Vernonia amygdalina.
Keywords: Antimicrobial activities; Leaf extract; Methanol extract; Phytochemicals; Vernonia amygdalina